Relationship between the Selected Factors with Entrepreneurial Intentions According To Students’ Perceptions - Hassan, Hisyamuddin (2007)
The main purpose of the study is to identify the relationship between the selected factors with entrepreneurial intentions according to students’ perceptions. The selected factors are attitudes towards entrepreneurship, entrepreneurship self-efficacy, subjective norms, proactive personality and teaching strategies. The method used in this study was descriptive-correlation which involved 166 students of Diploma in Entrepreneurship at Kolej Yayasan Melaka. The theoretical framework of the study was mainly based from the Ajzen-Fishbein’s intentions theory (1980), Shapero’s intentions model (1982), entrepreneurial intentions (Krueger & Carsrud, 1993), entrepreneurial self efficacy (Chen, Green & Crick, 1998) and the theory of proactive personality by Bateman and Crant (1993). The study utilised purposive sampling method (n=166) and Pearson Product Moment Correlation r was applied as a main statistical analysis for the study. The data was analysed at p<.01 significant level. The instrument used was modified based on several sources of past studies and had gone through a content validity process. The instrument has a reliability value with a Cronbach α range between .74 to .90. The results show that all the selected factors have a positive and significant correlation with entrepreneurial intentions. Attitudes towards entrepreneurship has the strongest relationship with entrepreneurial intentions (r=.69, p<.01), followed by subjective norms (r=.62, p<.01). Meanwhile, entrepreneurship self-efficacy (r=.48, p<.01), proactive personality (r=.41, p<.01), teacher centered teaching strategies (r=40, p<.01) and student centered teaching strategies (r=34, p<.01) have moderate and significant relationship with entrepreneurial intentions. As a conclusion, all the selected factors showed a significant and positive relationship with entrepreneurial intentions and both teaching strategies are equally important in determining entrepreneurial intentions based on students’ perceptions.